Music alone: Philosophical reflections on the purely musical experience - Kivy, Peter 1934-2017 (London Cornell University Press, 1991)
What makes a musical work profound? What is it about pure instrumental music that the listener finds attractive and rewarding? In addressing these questions, Peter Kivy continues his highly regarded exploration of the philosophy of musical aesthetics. He considers here what he believes to be the most difficult subject of all--"just plain music; music unaccompanied by text, title, subject, program, or plot; in other words, music alone."